„Ozdobiona wszelkimi cnotami” cesarska siostra Pulcheria i „roztropna” cesarzowa Atenais-Eudocja – co o epoce Teodozjusza II wiedzieli Słowianie prawosławni w średniowieczu? - Brzozowska, Zofia; Leszka, Mirosław J. (Vox Patrum, 2023)
The image of the Byzantine Empire in the mid-fifth century and the perception of its rulers in the Old Rus’ writing was formed on the basis of the Orthodox Slavonic translations created in the Balkans of the works of three Byzantine historians: John Malalas (sixth century), George the Monk called Hamartolos (ninth century), and Constantine Manasses (twelfth century). The use of their accounts by the authors of chronicles, even in the second half of the 16th century, testifies to the exceptional longevity of Byzantine historiography and the peculiar timelessness of the works of the aforementioned historians. It should be noted, however, that Pulcheria, Theodosius II, Athenais-Eudocia and Marcian did not only attract the attention of Old Rus’ historiographers as persons with real influence on the course of events in the past. Orthodox Slavs of the late Middle Ages viewed the mid-fifth century primarily as the era of the great disputes over the nature of Christ, culminating in the convening of the ecumenical councils of Ephesus (431) and Chalcedon (451). Some of the emperors and empresses involved in the theological controversies of their time were venerated as saints in the realm of Slavia Orthodoxa. Analysis of the Old Rus’ chronicles from the 14th-16th centuries allows us to assume that hagiography influenced the creation of the images of such figures in historiography. In order to reconstruct the overall image of Pulcheria and Athenais-Eudokia in Old Rus’ literature, it would therefore be necessary to examine the hagiographic texts dedicated to them.